Perancangan Sistem Informasi Penjualan dengan Metode Economic Order Quantity untuk Efisiensi Persediaan Barang menggunakan Metode Waterfall Berbasis Web Pada Toko Sembako Anugerah - Stefanus Yudhatama; Rusito Rusito; Sumaryanto Sumaryanto; Maya Utami Dewi; Migunani Migunani (Jurnal Manajemen Informatika & Teknologi, 2026)
For the operation of a retail business, such as a grocery establishment, meticulous inventory management is of paramount importance. Deficiencies in managing stock can precipitate situations of excess inventory, which invariably translate into financial losses for the owner. The Anugerah grocery store presently employs a conventional approach involving manual recording of sales figures and inventory, a system that is susceptible to recording errors, including the dual listing of purchases on checklists, and challenges in responding to frequent customer queries about item availability. Consequently, there is a clear requirement for a system that can systematically administer sales and inventory data. The core objective of this investigation is to conceptualize and construct a web-based sales information system that integrates the Economic Order Quantity (EOQ) framework. It is important to note that the EOQ method's utility lies in its analytical insights rather than its direct application for specifying exact order quantities. Furthermore, the system will incorporate algorithms for the comprehensive management of product details, sales processes, and transactional oversight. Through the deployment of this system, it is projected that the Anugerah grocery store will achieve a more streamlined, productive, and organized approach to its sales and inventory operations..